Gamification in Learning Management System: A study on Arabic e-learning - Wulandari Irma; Nur Hasim Jauari Akhmad; Damastuti Fardani Annisa; Pramulen Aji Sapta; Fananda Ibrohim Yofid; Amrullah Muhammad Akmal (SHS Web of Conferences)
Arabic has a vital role in the development of Islamic science, and it is used in the Al-Quran, Hadith, and books of Islamic Scholars. The Islamic Boarding School called Pesma Thaybah provides both education and Arabic learning. Design thinking-based e-learning design is an innovative approach to learning Arabic. The main problem of this research is how to design effective e-learning and add gamification to the learning management system. Then usability testing is applied, resulting in 100% effectiveness, meaning all students improved their learning outcomes. Testing for pre-test and post-test scores also increased by an average of 45%, indicating a significant improvement in learning. So, we can conclude that gamification can enhance the learning outcome at Pesma Thaybah.